Role of vacuum assisted closure therapy in chronic wounds: for some cases in Navi Mumbai - Gupta, Shitiz; Gupta, Shikha; Shaikh, Tanveer Parvez; Wani, Jatin B.; Gujar, Ajay; Bagul, Abhijit; Gautam, Raj; Narwade, Nandkishor; Miglani, Sonia (International Journal of Research in Medical Sciences, 2016)
Background: This study was performed to evaluate the results of vacuum assisted wound therapy in patients with chronic non healing ulcer. Methods: The study was conducted in the department of General Surgery at a tertiary care hospital. It was an observational study with prospective design. The role of NPWT in various wounds was studied in 10 patients. Results: Out of 10 wounds taken in the study, 7 wounds reduced in area & were resurfaced with Split thickness skin grafting and 3 wounds showed reduction in area & were subjected to secondary closure. Conclusions: Vacuum assisted closure (VAC) therapy provides sterile and controlled environment to large, exudating wound surfaces and is treatment of choice in infected / non – healing wounds, not responding to standard treatment.